Exploring the impact of critical thinking and digital literacy on students’ academic essay writing skills - Haliq, Abdul; Mahande, Ridwan Daud; Akhiruddin, Akhiruddin (Diksi, 2025)
This study explores the influence of critical thinking skills and digital literacy on academic essay-writing skills among university students. Employing an associative quantitative approach, it examines the relationship between two independent variables—critical thinking skills and digital literacy—and the dependent variable, academic essay-writing ability. Data were collected through a cross-sectional survey of a sample of 150 students selected using simple random sampling and analyzed using Structural Equation Modeling (SEM) with SmartPLS software. The findings reveal that critical thinking skills exert a significant and dominant influence on academic essay-writing ability, whereas digital literacy makes a smaller but still significant contribution. These results underscore the importance of integrating critical thinking skills and digital literacy into the educational curriculum as a strategy to enhance the quality of students’ academic writing. This research also offers recommendations for educators and policymakers to design more effective learning approaches that support the development of students’ 21st-century skills.